The Effect of Mindfulness and Spiritual Combination Breathing Exercises towards Anxiety, Depression and Blood Pressure of Ischemic Stroke Patients - Anie Tri Indiartinie; Eppy Setiyowati; Mulyadi (Journal of Nursing Practice)
Background: Ischemic stroke causes serious ongoing problems in the lives of sufferers, including biological, psychological and spiritual changes so that comprehensive and multidisciplinary nursing care is necessary.